Molecular Detection of Human Cytomegalovirus in Renal Failure Patients Using RT-Qpcr - Issa, Wafaa Abdulkadhim; Wijdan Abbas Eneama; Salah Naser (Indonesian Journal on Health Science and Medicine, 2025)
Abstract. This study aimed to detect Human Cytomegalovirus (CMV) in patients with renal failure using RT-qPCR. A total of 100 blood and serum samples were collected from July to September 2023 from individuals aged 1 to 80 years. The RT-qPCR technique revealed 79 positive cases of CMV infection. The study population was divided into five age groups, with the 51–67 age group showing the highest infection rate (29.11%). Infections were more common in females (41 cases) than in males (38 cases). The use of real-time PCR demonstrated a rapid, sensitive, and specific diagnostic tool for CMV, especially among immunocompromised patients. These findings suggest a significant association between CMV infection and renal failure, emphasizing the need for molecular testing in clinical diagnostics. The study provides valuable epidemiological insight and supports the implementation of RT-qPCR for detecting CMV in Iraqi healthcare settings. Highlights: RT-qPCR detected CMV infection in 79% of renal failure patients, confirming its high prevalence. Older adults (51–67 years) showed the highest infection rate, with females slightly more affected than males. RT-qPCR proved to be a rapid, sensitive, and reliable diagnostic tool for CMV detection in immunocompromised patients.